Evaluation of antibacterial effects of Zataria multiﬂora Boiss extracts against ESBL-producing Klebsiella pneumoniae strains - Dadashi, Masoud (Avicenna J Phytomed, 2016)
OBJECTIVE: There are few therapeutic options for treatment of multidrug resistant Klebsiella pneumoniae isolates as a hospital infectious agent (nosocomial infection). The aim of this study was to evaluate the antibacterial activity of Zataria multiﬂora Boiss extracts against ESBL-producing Klebsiella pneumoniae strains. MATERIALS AND METHODS: This study was conducted on 100 K. pneumoniae isolates from two hospitals in Tehran, Iran. Antibiotic susceptibility tests were performed by Kirby-Bauer disc diffusion and microdilution broth methods and detection of ESBL was carried out according to CLSI guidelines. The blaCTX-M-15 plasmid gene was detected by PCR and sequencing methods. Extracts susceptibility test was performed by broth microdilution method. RESULTS: Among 100 K. pneumoniae strains, 48 (48%) were ESBL positive. In this study, fosfomycin, colistin and tigecycline were more active than other antibiotics. The existence of blaCTX-M-15 was detected in 30 (62.5%) of 48 ESBL-producing isolates. The chloroformic extract showed potent activity against ESBL-producing K. pneumoniae strains (MIC(50 )= 1.56 mg/ml and MIC(90)=3.12mg/ml). The MIC(50) and MIC(90 )(The MIC(50) represents the MIC value at which ≥50% of the isolates in a test population are inhibited and the MIC(90) represents the MIC value at which ≥90% of the strains within a test population are inhibited) were 3.12 and 6.25 mg/ml and 6.25 and 12.5 mg/ml for methanolic and acetonic extracts, respectively. CONCLUSION: The incidence of ESBL-producing K. pneumoniae is very high. Therefore, detection of ESBL-producing K. pneumoniae isolates is of great importance in identifying drug resistance patterns in K. pneumoniae isolates and in control of infections. Zataria multiflora may have the potential to be used against multidrug resistant organisms such as clinical isolates of ESBL-producing K. pneumoniae.